SISTEM INFORMASI GUDANG OBAT PADA UPT PUSKESMAS - Evanita Evanita; Dafiq Elok Noor Hannas (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
The need for medical supplies at a Technical Implementation Unit of the Center for Public Health is of paramount importance. But in reality UPT Puskesmas especially those located in small towns have not been able to control the availability of drugs effectively. Often there is a shortage of even running out of drugs when needed. Distribution of drugs that take a long time also becomes a barrier drug can be used in an effective and efficient. An information system on drug data management is expected to assist officers in the pharmacy to be able to control the stock of drugs that exist in a UPT Puskesmas. A stock drug can be known from the exit and entry of existing drugs. This system uses UML in its design and java as a programming language. With the drug warehouse information system, monthly statements of drug stocks become easier, the availability of drugs can be controlled so that patients who should get free medicines from Puskesmas do not need to redeem or change drugs in pharmacies because of Puskesmas that run out of drug stock.Keywords: Drugs, Java, Puskesmas, UML